Genome sequencing of SARS-CoV-2 omicron variants in Delhi reveals alterations in immunogenic regions in spike glycoprotein - Shikha, Sristy; Jogi, Mukesh Kumar; Jha, Ruchika; Kumar, Rana Amit; Sah, Tathagat; Singh, Pushpendra; Sagar, Ritu; Kumar, Anuj; Marwal, Robin; Ponnusamy, Kalaiarasan; Agarwal, Subhash Mohan; Kumar, R. Suresh; et al. (Frontiers in Immunology, 2023)
The SARS-CoV-2 omicron variants keep accumulating a large number of mutations in the spike (S) protein, which contributes to greater transmissibility and a rapid rise to dominance within populations. The identification of mutations and their affinity to the cellular angiotensinconverting enzyme-2 (ACE-2) receptor and immune evasion in the Delhi NCR region was under-acknowledged. The study identifies some mutations (Y505 reversion, G339H, and R346T/N) in genomes from Delhi, India and their probable implications for altering the immune response and binding affinity for ACE-2. The spike mutations have influenced the neutralizing activity of antibodies against the omicron variant, which shows partial immune escape. However, researchers are currently exploring various mitigation strategies to tackle the potential decline in efficacy or effectiveness against existing and future variants of SARS-CoV-2. These strategies include modifying vaccines to target specific variants, such as the omicron variant, developing multivalent vaccine formulations, and exploring alternative delivery methods. To address this, it is also necessary to understand the impact of these mutations from a different perspective, especially in terms of alterations in antigenic determinants. In this study, we have done whole genome sequencing (WGS) of SARS-CoV-2 in COVID-19 samples from Delhi, NCR, and analyzed the spike's mutation with an emphasis on antigenic alterations. The impact of mutation in terms of epitope formation, loss/gain of efficiency, and interaction of epitopes with antibodies has been studied. Some of the mutations or variant genomes seem to be the progenitors of the upcoming variants in India. Our analyses suggested that weakening interactions with antibodies may lead to immune resistance in the circulating genomes.